Judicial Regionalism's Thwarting of UN Security Council Chapter VII Punitive Cosmopolitanism: Measuring the Effects on International Jurisdictional Constitutionalism. Issue 2 (6th May 2015) - Solomon, Solon
Abstract : Under Chapter VII the UN Security Council has the authority to legally condemn certain behaviors by enacting binding measures on both states and individuals. This has been interpreted through measures undertaken by the Security Council, such as the institution of international tribunals on an inter-state level, and the imposition of sanctions on a personal level. Focusing on Africa and Europe, this Article aspires to demonstrate how regional actors have acted in order to undermine the UN Security Chapter VII punitive cosmopolitanism, either through the institution of regional criminal courts meant to antagonize the International Criminal Court or through judicial decisions that clearly negate the Council's sanctions regime. In order to preserve international punitive cosmopolitanism, the Article will proceed to develop how regional jurisdictional initiatives can be integrated in the general international constitutional order, in both the criminal and the civil/administrative field.